Enhancement of Gingival Tissue Adherence of Zirconia Implant Posts: In Vitro Study - Zühlke Alexandra; Gasik Michael; Shahramian Khalil; Närhi Timo; Bilotsky Yevgen; Kangasniemi Ilkka (MDPI, 2022)
Prevention of bacterial inflammation around dental implants (peri-implantitis) is one of the keys to success of the implantation and can be achieved by securing the gingival tissue-abutment interface preventing penetration of bacteria. Modern dental practice has adopted zirconia abutments in place of titanium, but the adhesion of gingival tissue to zirconia is inferior to titanium. The aim of this study was to assess and improve the adhesion of mucosal tissues to zirconia posts using sol-gel derived TiO2 coating following dynamic mechanical testing. The posts were cultivated with porcine bone-gingival tissue specimens in vitro for 7 and 14 days and then subjected to dynamic mechanical analysis simulating physiological loading at 1 Hz up to 50 mu m amplitude. In parallel in silico analysis of stresses and strains have been made simulating "the worst case" when the fixture fails in osseointegration while the abutment still holds. Results show treatment of zirconia can lead to double interface stiffness (static shear stiffness values from 5-10 to 17-23 kPa and dynamic from 20-50 to 60-125 kPa), invariant viscostiffness (from 5-35 to 45-90 kPa center dot s(alpha)) and material memory values (increased from 0.06-0.10 to 0.17-0.25), which is beneficial in preventing bacterial contamination in dental implants. This suggests TiO2-coated zirconia abutments may have a significant clinical benefit for prevention of the bacterial contamination.